Medications to reduce emergence coughing after general anaesthesia with tracheal intubation: a systematic review and network meta-analysis. (April 2020) - Tung, Alan; Fergusson, Nicholas A.; Ng, Nicole; Hu, Vivien; Dormuth, Colin; Griesdale, Donald E.G.
Abstract: Background: Emergence coughing can harm the patient following completion of surgery, but it is unclear which medication is most effective at reducing this event. We conducted a systematic review and network meta-analysis of RCTs to determine the medications' relative efficacies on decreasing moderate to severe emergence coughing after general anaesthesia. Medications studied were lidocaine (i.v., intracuff, topical, or tracheal application), dexmedetomidine, remifentanil, and fentanyl. Methods: We searched eight different medical literature databases, conference abstracts, and article references. After screening, included citations were evaluated for bias and had their data extracted. Pooled odds ratios and 95% confidence intervals for each treatment comparison were calculated. A surface under the cumulative ranking curve analysis (SUCRA) determined the relative rank of each intervention to decrease moderate to severe emergence coughing. Subgroup analyses included severe coughing only, extubation times, type of maintenance anaesthetic, and dosages. Results: The network meta-analysis included 70 studies and 5286 patients. All study medications had favourable odds in reducing moderate and severe peri-extubation coughing compared with either no medication or placebo. No single medication was favoured over another. Dexmedetomidine had the highest SUCRA rank, followed in order by remifentanil, fentanyl, and lidocaine via intracuff, tracheal/topical, and i.v. routes. Remifentanil was ranked highest for decreasing severe coughing only. Intracuff lidocaine had higher odds of prolonging extubation times compared with placebo, dexmedetomidine, fentanyl, and remifentanil. Conclusion: All study medications were better than placebo or no medication in reducing moderate to severe emergence cough, with dexmedetomidine ranked the most effective. Systematic review registration: PROSPERO registration number: CRD42018102870.